PELATIHAN PENGGUNAAN APLIKASI EDMODO DALAM MENUNJANG PROSES PEMBELAJARAN DI SMAN 1 CIOMAS - Fitri Aida Sari (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat Universitas Banten Jaya, 2020)
Mastery of technology is one aspect that teachers and students must have. Learning that is not accompanied by using of technology, will make learning difficult to develop. Edmodo is a technology-based application that is accessed online and can help teachers carry out learning. Edmodo has various features such as creating online classes, arranging agendas, doing digital storage, even teachers can create quizzes, assignments or exams that teachers can design, such as national exams. The purpose of this community service program is to introduce students to what edmodo is and how to use it. The training was carried out by providing materials and tutorials on how to use edmodo. After that, students are welcome to practice using Edmodo and the presenters monitor the practice of the students. Based on interviews conducted with students related to training in the use of edmodo, it was concluded that students felt tremendous benefits from this training and hoped that technology-based learning, especially using edmodo, could be applied by teachers in their schools.